Comparison of the effects of explicit and implicit learning on the balance of the elderly - Parichehr Farhangiyan; Gholamhossein Nazemzadegan; Usef Garmanjani (Sport Sciences and Health Research)
Background: In recent years, the examination of the impact of various types of different exercises as the key influential components on balance has gained considerable popularity. Numerous studies have investigated the effects of diverse exercise modalities on the enhancement of balance abilities. Aim: The aim of this research was to compare the effects of different types of learning (explicit and implicit) on the balance of elderly individuals. Materials and Methods: Forty-two elderly participants (both women and men), after initial health assessments and medical history reviews, voluntarily participated in the study. They were randomly assigned to three groups: explicit learning group (14 participants), implicit learning group (14 participants), and control group (14 participants). Before the implementation of the targeted learning exercises, the static balance of the participants was assessed using the Flamingo Test, and dynamic balance was measured using the Timed Up and Go (TUG) test. After two sessions of learning exercises, the participants were reassessed. Statistical analysis was conducted using descriptive statistics (mean and standard deviation) and inferential statistics (ANCOVA and Shapiro-Wilk test) at a significance level of P<0.05. Results: The findings indicated that there was no significant difference between the groups in the pre-test, but after performing the learning exercises, the static balance of the implicit learning group showed a statistically significant improvement compared to the explicit learning group and the control group. However, there was no significant increase in dynamic balance performance in any of the groups. Conclusion: The results of this study support the claim that implicit learning exercises can have a positive and significant impact on the static balance performance of elderly individuals. It was also shown that implicit cognitive training had no effect on dynamic balance, which may indicate the important role of other variables such as motor control abilities.